Pengembangan Kreativitas Santri dalam Pengelolaan Sampah Bernilai Ekonomis di PP. Miftahul Mubtadiin Krempyang Nganjuk - M. Yusuf; Ahmad Saifudin (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
This mentoring program is oriented towards the pesantren community at the Miftahul Mubtadiin Putri Ar-ridlo Islamic Boarding School in the field of non-organic waste utilization. This activity is carried out to develop the potential of students through life skill coaching in the form of utilizing non-organic waste for economic value. This program aims to make the accumulated waste useful and have use value, so that through this community service activity it will be directed at the use of valueless items into products that have selling value in the economic development of the pesantren. If this program is successful, it can reduce the amount of waste available and can be a more useful asset to be developed in the pesantren environment. The methods used in this mentoring are lectures and demonstration methods. From this mentoring process, the students have become more creative in managing non-organic waste in the pesantren. Then the waste is managed properly into useful items. This program aims to produce girls who are not only competent in the spiritual field but also have provisions in managing the wheels of the economy.